2013
DOI: 10.1016/j.plipres.2012.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and the role of saturated fatty acids in the progression of non-alcoholic fatty liver disease

Abstract: The steady rise in Western obesity rates has been closely linked to significant increases in a multitude of accompanying health problems including Non-Alcoholic Fatty Liver Disease (NAFLD). NAFLD severity ranges from simple steatosis to acute steatohepatitis, but the molecular mechanisms controlling progression of this disease are poorly understood. Recent literature suggests that elevated free fatty acids (FFAs), especially saturated FFAs, may play an important role in lipotoxic mechanisms, both in experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
251
2
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(267 citation statements)
references
References 114 publications
9
251
2
5
Order By: Relevance
“…This implies that, when we analyse the effect of treatment as a dichotomous variable (improvement vs no improvement in fibrosis), there is no significant difference between arms (4/16 patients with improved fibrosis stage following ezetimibe compared with 1/12 in controls, p=0.136 with χ 2 test). While the impact on liver fibrosis needs further confirmation in larger studies, given the small number of patients included, the findings of this trial corroborate recent results from experimental models, suggesting that hepatic accumulation of non-triacylglycerol toxic lipid species (non-esterified cholesterol, saturated fatty acids, ceramides and diacylglycerols) triggers endoplasmic reticulum stress, mitochondrial dysfunction and oxidative stress, promoting liver injury, steatohepatitis and fibrosis [5,[7][8][9][10]. Several putative mechanisms linking cholesterol accumulation to hepatic stellate cell (HSC) activation and fibrogenesis have been demonstrated experimentally and reviewed elsewhere [5], including enhanced toll-like receptor (TLR)-4 pathway activation, which sensitises HSCs to the key fibrogenic factor transforming growth factor (TGF)-β1 [10], and reduces AMP-activated protein kinase-α (AMPK) activation [11] ( Fig.…”
Section: Ezetimibe Treatment Was Associated With An Increase Insupporting
confidence: 81%
“…This implies that, when we analyse the effect of treatment as a dichotomous variable (improvement vs no improvement in fibrosis), there is no significant difference between arms (4/16 patients with improved fibrosis stage following ezetimibe compared with 1/12 in controls, p=0.136 with χ 2 test). While the impact on liver fibrosis needs further confirmation in larger studies, given the small number of patients included, the findings of this trial corroborate recent results from experimental models, suggesting that hepatic accumulation of non-triacylglycerol toxic lipid species (non-esterified cholesterol, saturated fatty acids, ceramides and diacylglycerols) triggers endoplasmic reticulum stress, mitochondrial dysfunction and oxidative stress, promoting liver injury, steatohepatitis and fibrosis [5,[7][8][9][10]. Several putative mechanisms linking cholesterol accumulation to hepatic stellate cell (HSC) activation and fibrogenesis have been demonstrated experimentally and reviewed elsewhere [5], including enhanced toll-like receptor (TLR)-4 pathway activation, which sensitises HSCs to the key fibrogenic factor transforming growth factor (TGF)-β1 [10], and reduces AMP-activated protein kinase-α (AMPK) activation [11] ( Fig.…”
Section: Ezetimibe Treatment Was Associated With An Increase Insupporting
confidence: 81%
“…Hepatocyte apoptosis is a common in NASH as a result of lipotoxicity and endoplasmic reticulum stress (Leamy et al, 2013 andGentile et al, 2011). We have observed that annexin 5 stains intracellular lipid vesicles in F4/80 + cells, suggesting that the phagocytosis of apoptotic bodies derived from dead fat-laden hepatocytes might contribute to AnxA1 up-regulation.…”
Section: Discussionmentioning
confidence: 90%
“…A recent study from our laboratory demonstrated that dietary fat composition (i.e., saturated vs. unsaturated) had a profound effect on deleterious liver outcomes, including ER stress, liver weight, and hepatic steatosis, which are components of NAFLD ( 22,(26)(27)(28)(29)(30). Moreover, other studies in our laboratory and others indicated that palmitate (C16:0), but not oleate (C18:1), increased expression of SphK1 in skeletal muscle, and that the enzyme was required for expression of proinfl ammatory genes in primary skeletal muscle cells and also in skeletal muscle in mice on a highfat diet ( 7,13 ).…”
Section: Resultsmentioning
confidence: 99%
“…It should be stated, however, that fi ndings herein may be limited to situations where individuals consume a diet high in saturated fat. In fact, these data may shed light on well-known associations between saturated fat and metabolic disease severity and, in particular, NAFLD ( 28 ). Some limitations of this study include the use of a wholebody knockout, in which the metabolic characteristics of the HSFD, including weight gain, percent increase in fasting glucose (though total fasting glucose was higher than in the WT mice), and hyperinsulinemia, were partially attenuated.…”
Section: Receptor-mediated S1p Proinfl Ammatory Signaling In Hepg2 Cellsmentioning
confidence: 92%